Sandwich-Structured h-BN/PVDF/h-BN Film With High Dielectric Strength and Energy Storage Density - Meng, Guodong; She, Junyi; Wang, Changling; Wang, Wenke; Pan, Cheng; Cheng, Yonghong (Frontiers in Chemistry, 2022)
Energy storage film is one of the most important energy storage materials, while the performance of commercial energy storage films currently cannot meet the growing industrial requirements. Hence, this work presents a h-BN/PVDF/h-BN sandwich composite structure film prepared by laminating a large area of ultra-thin hexagonal boron nitride (h-BN) and polyvinylidene fluoride (PVDF), the existence of which was confirmed by optical microscope and elemental composition analysis based on scanning electron microscopy and X-ray diffraction. This film has an ultra-high dielectric strength of 464.7 kV/mm and a discharged energy density of up to 19.256 J/cm3, which is much larger than the commercial energy storage film biaxially oriented polypropylene (BOPP) (<2.5 J/cm3). Although the thickness of h-BN film is only 70 nm compared with that of PVDF (about 12 μm), the dielectric strength of the sandwich-structured film presents a great increase. It is because of the excellent insulation performance of the h-BN film that helps to resist the electron injection and migration under high electric field, and then suppress the formation and growth of the breakdown path, leading to an improvement of the charge-discharge efficiency.